PENGARUH IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAHAN (SAP) DAN SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) TERHADAP KUALITAS LAPORAN KEUANGAN PADA PEMERINTAHAN DAERAH KABUPATEN KUNINGAN - Suhaeti, Nunung; Suhendar, Dadang (Program Studi Akuntansi, Universitas Kuningan, 2015)
This research is done at kuningan District, it began on February until May 2015, this research aimed to knowing the Effect of the Implementation of Government Accounting Standards and Internal Control System of Government on the Quality of Financial Report. This research used descriptive research method and verificative data collecting method which used quisioner, research objectis 37 respondents whom the chief of area work unit at Kuningan, sampling methods used research sampling techniques. Data refineries technique used this research is Spearman Rank correlation technique. Based on the Spearman Rank correlation coefficient calculation partially for X1 with using Y about 0,831 it means there is strong connection between the Implementation of Government Accounting Standards with Quality of Financial Report (SAP). While for X2 with Y about 0,917 it means that there is strong connection between Internal Control System of Government with Quality of Financial Report (SPIP). Simultaneous correlation coefficient based analysis result is taken summaryÃ‚Â that the Implementation of Government Accounting Standard (SAP) and Internal Control Systems of Government on the Quality of Financial Report (SPIP) be important Effect toward quality of Financial reports. While based on this counting can be known determination coefficient (r2) is 90,30 %. This thing showed that the Effect is given by variable of Implementation of Government Accounting Standards (SAP) and Internal Control System of Government on the Quality of Financial Report (SPIP). Toward quality of financial report simultaneously in the amount of 90,3 % while remain 9,7 % is affected by the orther factors wich are not researched in this research. Thus this research hypothesis stated the Implmentation of Government Accounting Standards (SAP) and Internal Control System of Government on the Quality of Financial Report (SPIP) positive affected toward quality of financial report partially and simultanceous can be received and significant.Ã‚Â